Bir antrenman diliminde beceriye ilişkin çalışmaların öncelik sıralamasının performansa etkisinin incelenmesi - Akın, Hanife Kübra (My University, 2019)
Bir Antrenman Diliminde Beceriye İlişkin Çalışmaların Öncelik Sıralamasının Performansa Etkisinin İncelenmesiÖğrencinin Adı: Hanife Kübra AKIN Danışman: Prof. Dr. Salih PINARAnabilim Dalı: Beden Eğitimi ve Spor Amaç: Bir antrenman diliminde beceriye ilişkin çalışmaların(sürat, çeviklik, denge, esneklik ve koordinasyon) öncelik sıralamasının performansa etkileri belirlenerek, testlerin antrenman öncesi veya sonrası yapıldığındaki farklılıklar belirlenerek, yorgunluğun sporcular üzerindeki etkileri görülecek, ayrıca devam eden antrenman süreçlerindeki gelişimleri incelenecektir. Gereç ve Yöntem: Çalışmaya Beşiktaş Jimnastik Kulübü U-16 takım sporcularından 20 kişi gönüllü olarak katılmıştır. Çalışmada sporcuların esnekliklerini ölçmek amacıyla Otur-Eriş Testi, çevikliklerini ölçmek amacıyla İlionis Testi, süratlerini ölçmek için 30 mt. Sürat Testi, denge ve koordinasyonlarını belirlemek içinse Flamingo Denge Testi ve Burpee Testleri uygulanmıştır. Ölçümlerden önce ısınma protokolü uygulanmıştır. Toplamda 4 test yapılmış, testler takımın tümüne ve 3 gün aralıkla, antrenman öncesinde ve sonrasında olacak şekilde toplamda 4 test uygulanmıştır.Bulgular: Çalışmada elde edilen sonuçlar arasındaki farklar SPSS 21 kullanılarak Eş Örneklem T Testi analizi ile 0,05 anlamlılık düzeyinde incelenmiş ve çeşitli bulgulara ulaşılmıştır. Alınan verilerden yapılan istatistiksel sonuçlar doğrultusunda sporcularda, yapılan antrenman dilimindeki çalışmaların öncelik sıralamasının performansa ve yorgunluk durumlarına etkisinin olduğu ayrıca yorgunluğun performans üzerinde etkisi olduğu gözlemlenmiştir.Anahtar sözcükler: Antrenman, Performans, Sürat, Çeviklik, Denge, Koordinasyon becerisi, Bilimsel test

Examination of the Effect of Priority Sequencing of Exercises -Related to Skill- on Performance in a Training Period Student Name: Hanife Kübra AKIN, Prof. Dr. Salih PINAR, Department of Physical Education and SportsPurpose: By determining the effects of priority sequencing of exercises -related to skill- (speed, agility, balance, flexibility and coordination) on performance in a training period, and determining the differences among the trainings performed before and after the training, the effects of fatigue on athletes will be seen, also their developments at on-going training processes will be examined. Materials and Methods: To the field study its 20 volunteer U-16 team players joined from a Turkish football team (Beşiktaş Jimnastik Kulübü). To measure their flexibilities the sit-reach test applied on them, to measure agility the Illinois test, to measure speed the 30 mt. speed test, as for to measure balance and coordination the standing long jump and Burpee tests applied on them. Before measurements an exercise protocol used. Totally 4 tests applied; the tests have been applied on overall team after an interval of three days as before training and after training. Findings: Differences between the results obtained from the study examined using SPSS 21 program with analysis of Sample T Test for a significance level of 0,05, and in this way have been reached to various findings. In the direction of statistical results receiving from obtained data it has been observed that the order of priority of exercises in applied traning period have effect on athletes’ performance and fatigue situations, also fatigue has effect on performance.Training, Performance, Speed, Agility, Balance, Coordination skill, Scientific testsExamination of the Effect of Priority Sequencing of Exercises -Related to Skill- on Performance in a Training Period Student Name: Hanife Kübra AKIN, Prof. Dr. Salih PINAR, Department of Physical Education and SportsPurpose: By determining the effects of priority sequencing of exercises -related to skill- (speed, agility, balance, flexibility and coordination) on performance in a training period, and determining the differences among the trainings performed before and after the training, the effects of fatigue on athletes will be seen, also their developments at on-going training processes will be examined. Materials and Methods: To the field study its 20 volunteer U-16 team players joined from a Turkish football team (Beşiktaş Jimnastik Kulübü). To measure their flexibilities the sit-reach test applied on them, to measure agility the Illinois test, to measure speed the 30 mt. speed test, as for to measure balance and coordination the standing long jump and Burpee tests applied on them. Before measurements an exercise protocol used. Totally 4 tests applied; the tests have been applied on overall team after an interval of three days as before training and after training. Findings: Differences between the results obtained from the study examined using SPSS 21 program with analysis of Sample T Test for a significance level of 0,05, and in this way have been reached to various findings. In the direction of statistical results receiving from obtained data it has been observed that the order of priority of exercises in applied traning period have effect on athletes’ performance and fatigue situations, also fatigue has effect on performance.Training, Performance, Speed, Agility, Balance, Coordination skill, Scientific tests2. SUMMARYExamination of the Effect of Priority Sequencing of Exercises -Related to Skill- on Performance in a Training Period Student Name: Hanife Kübra AKIN, Prof. Dr. Salih PINAR, Department of Physical Education and SportsPurpose: By determining the effects of priority sequencing of exercises -related to skill- (speed, agility, balance, flexibility and coordination) on performance in a training period, and determining the differences among the trainings performed before and after the training, the effects of fatigue on athletes will be seen, also their developments at on-going training processes will be examined. Materials and Methods: To the field study its 20 volunteer U-16 team players joined from a Turkish football team (Beşiktaş Jimnastik Kulübü). To measure their flexibilities the sit-reach test applied on them, to measure agility the Illinois test, to measure speed the 30 mt. speed test, as for to measure balance and coordination the standing long jump and Burpee tests applied on them. Before measurements an exercise protocol used. Totally 4 tests applied; the tests have been applied on overall team after an interval of three days as before training and after training. Findings: Differences between the results obtained from the study examined using SPSS 21 program with analysis of Sample T Test for a significance level of 0,05, and in this way have been reached to various findings. In the direction of statistical results receiving from obtained data it has been observed that the order of priority of exercises in applied traning period have effect on athletes’ performance and fatigue situations, also fatigue has effect on performance.Training, Performance, Speed, Agility, Balance, Coordination skill, Scientific tests
Keywords: Agility; Antrenman; Balance; Bilimsel test Training; Coordination skill; Çeviklik; Denge; Education; Eğitim; Koordinasyon becerisi; Performance; Performans; Scientific tests; Speed; Spor; Sports; Sürat